Miniature self heating device for bioassay - Achmad Johari Mohammad Rashid (Nanyang Technological University, 2020)
The study on heating methods in bioassay procedures and the feasibility of utilizing modern 3D printing technology was executed. Loop-mediated Isothermal Amplification (LAMP) bioassay, which helps in the method of identifying DNA strands of certain diseases was focused on extensively and the performance of heating methods were evaluated in this study. The miniature self-heating device which would be used to carry out the LAMP bioassay was produced by using Stereolithography (SLA) and constructed from liquid resin. Elevated isothermal conditions will be present inside the device through the use of Phase Change Material. The heating methods consisting of exothermic chemical reactions were subsequently evaluated with careful guidance and measurements. Subsequently,comparison was done to determine the better heat generation method to be used in the miniature heating device in conjunction with the PCM for the LAMP bioassay. The design of the heating device was based on the dimensions that best suits the device to be portable and relatively easy to use. To determine which of the exothermic chemical reactions is better to be used in conjunction with the PCM, a series of chemical reaction tests were conducted and data measurements of temperatures that were obtained by the reactions were recorded and tabulated. Graphical representations were also shown to prove which of the heating methods could potentially be used for LAMP bioassay. A thermocouple was used in the temperature measurements of all the experiments at the reaction chamber of the 3D printed self-heating device. The chemical experiments were carried out by varying the weight of the chemical elements used for the exothermic reactions, namely dissolution of Calcium Chloride in excess of water and oxidation of pure Iron powder in excess of oxygen with activated carbon as well as saline water as a catalyst. Although the volume of the reaction chamber of the heating device was small, temperatures manage to surpass the melting point of the PCM rendering it to be a success in providing elevated isothermal conditions in the device itself. In this paper, experimental limitations difficulties faced during the whole project were also explained.